2017
DOI: 10.1007/s12600-017-0577-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synthetic insecticides on the larvae of Coccinella septempunctata from Greek populations

Abstract: Coccinella septempunctata L. is one of the most abundant ladybird species in Greece, preying on several aphid species and other arthropods, of which many are pests of cultivated plants. These pests are usually controlled with chemical insecticides. During this process, however, beneficials are also exposed to pesticides. The development of Integrated Pest Management (IPM) programs against aphids requires the evaluation of the effects of insecticides on beneficial insects. We evaluated the LD 50 of imidacloprid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 48 publications
4
15
0
Order By: Relevance
“…This conclusion is supported by previous observations that soil-applied imidacloprid is readily translocated into various tissues of C. pepo plants [17] and that the lethal effects of imidacloprid consumption on three different coccinellid species have been observed at 6.03 µg/g [18]. In general, imidacloprid is considered very toxic to coccinellid larvae, with lethal residues at concentrations as low as 2.6 µg/g [19] and lethal contact doses as low as 1.7 µg/g [20]. The levels of imidacloprid detected in the fungal conidia in our study exceeded all of these limits, even several weeks after the initial application of the insecticide material.…”
Section: Discussionsupporting
confidence: 85%
“…This conclusion is supported by previous observations that soil-applied imidacloprid is readily translocated into various tissues of C. pepo plants [17] and that the lethal effects of imidacloprid consumption on three different coccinellid species have been observed at 6.03 µg/g [18]. In general, imidacloprid is considered very toxic to coccinellid larvae, with lethal residues at concentrations as low as 2.6 µg/g [19] and lethal contact doses as low as 1.7 µg/g [20]. The levels of imidacloprid detected in the fungal conidia in our study exceeded all of these limits, even several weeks after the initial application of the insecticide material.…”
Section: Discussionsupporting
confidence: 85%
“…These authors raised the concern that such complex behavioral changes in invasive ants might occur with other beneficial ant species upon exposure to neonicotinoids. Low levels of imidacloprid affected ladybugs by reducing their consumption of aphids, ultimately reducing adult body weight and inducing slower development, underlining the relevance of looking into effects on predatory species [120]. This agrees with Bredeson et al [121] who reported altered quality of Rhopalosiphum padi aphids for the predatory species C. maculata upon exposure to thiamethoxam.…”
Section: Effects Of Insecticides At Individual and Population Levelssupporting
confidence: 82%
“…Imidacloprid has been found to reduce fecundity in coccinellids such as H. variegata and Nephaspis oculata [14,32] and affected predators' functional responses in Serangium japonicum and Harmonia axyridis (Colleoptera: Coccinellidae) [33,34]. On the other hand, only limited data are available on the impact of deltamethrin on Coccinellid predators [35].…”
Section: Introductionmentioning
confidence: 99%